Potential, challenges and pitfalls of pay-for-performance schemes: a narrative review evaluating the merits for the Australian home care sector. Issue 1 (20th August 2021) - Veen, Alex; Bartram, Timothy; Cooke, Fang Lee
Abstract : Purpose: This qualitative narrative review aims to identify and evaluate the potential, challenges and pitfalls of pay-for-performance (P4P) schemes for the home care of adults with a disability. Due to a limited experimentation with P4P schemes in the context of the home and disability care sectors, the authors conducted a narrative review focusing on related areas of care, primarily nursing home care, to better understand the effectiveness of P4P schemes as a care intervention and evaluate the challenges associated with the introduction of these schemes. Design/methodology/approach: The authors employed a narrative review approach to examine the effectiveness of P4P schemes as a care intervention. The approach included a manual content analysis of the relevant academic and grey literature, focusing on the potential, challenges and pitfalls of P4P for care funders and providers. Findings: There is some, albeit limited, evidence from other related areas of care to support the effectiveness of P4P to improve the quality of care or the efficiency of its delivery for the home care sector. The results of prior studies are, however, often mixed and inconclusive, due to flaws with the design of schemes, including the nature of the incentives. Limited duration and poor-quality evaluations have further hampered the ability of studies to demonstrate the effectiveness of P4P schemes, which diminishes the credibility of these care interventions. When undertaken systematically, there seems to be some evidence that P4P can work; however, it requires careful design, implementation, measurement and evaluation. Practical implications: Based on the challenges associated with the successful implementation of P4P schemes, the authors identified lessons for the design, implementation, measurement and evaluation of P4P schemes for care funders and policymakers. Originality/value: This study critically evaluates the potential of P4P as a care intervention for the home care and disability sectors. By evaluating the potential, challenges and pitfalls associated with P4P in related areas of care, the study provides guidance to home care funders, providers and policymakers in care settings.